The Predictive Value of the Systemic Immune-Inflammation Index for Cardiovascular Events in Chronic Total Occlusion Patients Who Prior Coronary Artery Bypass Grafting - Zhao Y; Zhao S; Shi Y; Ma Q; Zheng Z; Wang P; Liu J (Dove Medical Press, 2024)
Yuhao Zhao,* Shun Zhao,* Yuchen Shi, Qin Ma, Ze Zheng, Ping Wang, Jinghua Liu Center for Coronary Artery Disease (CCAD), Beijing Anzhen Hospital, Capital Medical University, and Beijing Institute of Heart, Lung and Blood Vessel Diseases, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Ping Wang; Jinghua Liu, Email wang_ping@vip.sina.com; liujinghua@vip.sina.comBackground: There is limited research on the long-term prognosis of percutaneous coronary intervention (PCI) in coronary chronic total occlusion (CTO) patients who have previously undergone coronary artery bypass grafting (CABG). Additionally, the prognostic value of a novel systemic immune inflammation index (SII) in this specific patient population remains unclear.Methods: To adjust for differences in baseline features and minimize bias, 335 pairs of patients with or without prior CABG undergone PCI were obtained after probability score matching (PSM) in a single-center cohort. The clinical characteristics were collected, and the primary outcomes were major cardiovascular events (MACE), which included all-cause death, nonfatal MI and unplanned revascularization, were recorded during the follow-up period after discharge. The group with prior CABG were divided according to the median level of SII: Lower SII group (SII ≤ 570.10, N = 167) and higher SII group (SII ≥ 570.10, N = 168).Results: The SII values were significantly higher in the prior CABG group than in the without prior CABG group [570.10 (444.60, 814.12) vs 519.65 (446.86, 565.84), P < 0.001, respectively]. The survival Kaplan-Meier analysis showed that patients with prior CABG was significantly associated with a higher risk of MACE than patients without prior CABG (P = 0.016) in the long-term follow-up. As SII levels increased, the cumulative risk of MACE became significantly higher in the patients with prior CABG (P = 0.023) stratified by the median value of SII. The Cox proportional hazards regression model analysis indicated that the level of SII (hazard ratio = 2.035, 95% CI, 1.103- 3.753, P = 0.023) emerged as independent predictors of MACE. The restricted cubic spline (RCS) analysis illustrated that the HR for MACE increased with increasing SII.Conclusion: SII is a reliable predictor of long-term cardiovascular events after PCI in CTO patients with prior CABG, suggesting that SII may be helpful in identifying high-risk patients who need more aggressive treatment and follow‐up strategies.Keywords: systemic immune inflammation index, coronary chronic total occlusion, coronary artery bypass grafting, percutaneous coronary intervention, major adverse cardiovascular events